Edukasi Dan Pelatihan Administrasi Terhadap Santri Putri Pondok Pesantren Mbah Ashfiya’ Di Desa Pranggang Kecamatan Plosoklaten Kabupaten Kediri - Qurrotul Muzdalifah; Uzeir Mustaghfirin (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
Financial statements are basically the result of an accounting process that can be used as a tool to communicate financial data or company activities to interested parties. The financial statements were also prepared by the student daughter of Pondok Pesantren Mbah Ashfiya' as one of the business responsibilities that have been carried out which will later be reported to the caretaker of Pondok Pesantren Mbah Ashfiya'. In addition, financial statements are also useful to find out the real condition of business finance, regulate and control financial transactions that occur throughout the overall sustainability of the business. Financial statements can also be the basis of economic decision making in business management such as pricing and others. But in its realization, the student daughter of Pondok Pesantren Mbah Ashfiya' had difficulty in terms of making simple financial statements and transaction bookkeeping. Therefore, researchers took the initiative to conduct "Education and Administrative Training on Santri Putri Pondok Pesantren Mbah Ashfiya' in Pranggang Village, Plosoklaten District, Kediri Regency" which was considered very suitable to overcome the above problems. In this study, we used the PAR (Participatory Action Research) method. PAR method is a study or applied research that involves researchers or actors of devotion or empowerment to take a role. By directly participating in conducting education and administrative training on the students of Pondok Pesantren Mbah Ashfiya' Kediri which is carried out in 2 implementation methods, namely online and face to face which is expected to form skills, insights and understanding in terms of reporting and good archival administration.